2000
DOI: 10.1111/1469-7610.00635
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐term Psychological Effects of a Disaster Experienced in Adolescence: I: The Incidence and Course of PTSD

Abstract: Previous studies have shown that children and adolescents exposed to traumatic experience in a disaster can suffer from high levels of post-traumatic stress. The present paper is the first a series reporting on the long-term follow-up of a group of young adults who as teenagers had survived a shipping disaster-the sinking of the "Jupiter" in Greek waters-between 5 and 8 years previously. The general methodology of the follow-up study as a whole is described, and the incidence and long-term course of Post-Traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(172 citation statements)
references
References 40 publications
9
156
0
5
Order By: Relevance
“…PTSD may be chronic in youth, potentially lasting years (Morgan, Scourfield, Williams, Jasper, & Lewis, 2003; Yule et al., 2000). Given this potential for profound disruption of a young person's development, researchers have attempted to understand the etiology and evolution of chronic PTSD (Winston, Kassam‐Adams, & Garcia‐Espana, 2003), with a view to early intervention (Marsac, Donlon, & Berkowitz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PTSD may be chronic in youth, potentially lasting years (Morgan, Scourfield, Williams, Jasper, & Lewis, 2003; Yule et al., 2000). Given this potential for profound disruption of a young person's development, researchers have attempted to understand the etiology and evolution of chronic PTSD (Winston, Kassam‐Adams, & Garcia‐Espana, 2003), with a view to early intervention (Marsac, Donlon, & Berkowitz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Houston et al (2008) found an interaction between cannabis use, childhood sexual abuse, and adult non-affective psychosis. Several previous studies have followed the childhood survivors of natural disasters into adulthood (Green et al, 1994;Yule et al, 2000;Bolton et al, 2000;Morgan et al, 2003), but none of these studies have investigated the prevalence of SPE in the survivors when they reach adulthood. Further, none have included control subjects recruited during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of PTSD in populations exposed to severe trauma are even higher. [3][4][5][6][7][8] PTSD often has a chronic course, and symptoms may be disabling. 1 Exposure to a traumatic stressor is essential to the diagnosis of PTSD.…”
Section: Introductionmentioning
confidence: 99%